The Influence of Initial Normal Stress Assumption of Slip Surface on Safety Factor of Symmetrical Three-Dimensional Slopes - Huali Liu (Advances in Materials Science and Engineering)
By using the explicit solution of three-dimensional slope stability based on modification of normal stress distribution over the slip surface, the influence of assumption of the three-dimensional initial normal stress on the safety factor is investigated. The initial normal stress distribution over the 3D slip surface was assumed, and then it was modified by a function with 2 parameters to satisfy two force equilibrium conditions about two axes and one moment equilibrium condition around one axis. An iterative equation was derived that would yield a value to 3D safety factor. The values of three-dimensional safety factor of symmetrical slopes are computed with different assumptions of initial normal stresses. The computation results show that the influence of assumption of initial normal stress on the safety factor of symmetrical three-dimensional slopes is negligible because the maximum different value of the three-dimensional safety factor is below 5%.